Approximation by de la Vallée-Poussin operators on the classes of functions locally summable on the real axis - Rukasov, V. I.; Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For the least upper bounds of deviations of the de la Vallée-Poussin operators on the classes $\widehat{L}^{ψ}_{β}$ of rapidly vanishing functions $ψ$ in the metric of the spaces $\widehat{L}_p,\; 1 ≤ p ≤ ∞$, we establish upper estimates that are exact on some subsets of functions from $\widehat{L}_p$.